Long term results of RFA to lung metastases from colorectal cancer in 157 patients. Issue 5 (May 2015) - Ferguson, J.; Alzahrani, N.; Zhao, J.; Glenn, D.; Power, M.; Liauw, W.; Morris, D.L.
Abstract Introduction We evaluated the long-term outcomes of 157 patients receiving radiofrequency ablation (RFA) to colorectal cancer (CRC) lung metastases. Methods A total of 434 lesions were ablated in 199 procedures over 14 years. Thirty-two out of the 157 patients underwent multiple procedures. Our primary end-points were overall survival, disease free survival, procedure-related mortality and morbidity and various prognostic entities for survival. The survival in three subgroups were analysed: those that had undergone CRC resection and peritonectomy, CRC resection and liver resection and resection of their primary CRC alone. Results 105 patients (67%) underwent pre-RFA liver resections, 14 patients (9%) underwent pre-RFA peritonectomies and 58 patients underwent only resection of their primary tumour. There were no procedurally related deaths. The mean duration of follow up was 28 months. A chest drain was required in 18.6% of all procedures. The overall median survival was 33.3 months. Survival at 1, 3 and 5 years was 89, 44 and 19.9% respectively. RFA post liver resection, post peritonectomy and post primary CRC resection alone saw median survivals of 38 months, 26 months and 27 months respectively. Tumour free survival at 12 months, 3 years and 5 years was 60.5%, 14.4% and 7% respectively. Lesion size, lesion number and pre-RFA CEA levels were not prognostic factors for overall survival or disease free survival. Conclusion RFA is now an accepted alternative treatment modality for CRC lung metastases in selected groups of patients. RFA has a reasonable morbidity profile and a demonstrated benefit for survival in these patients.